Paraquat poisoning: a grim prognosis and urgent need for policy action – a case series - Hamsa C. Maheshwarappa; Krishnkant Bhardwaj; Pradeep Moolchandani; Gowthaman T. B.; Saurabh Saigal (International Journal of Advances in Medicine, 2026)
Paraquat is a highly toxic, rapidly acting, non-selective herbicide with widespread use in India despite being banned in many countries. It is associated with a high mortality rate and lacks a specific antidote. Aim and objective were to present a case series of paraquat poisoning, highlighting clinical presentation, complications, treatment modalities, and outcomes. Emphasizing the importance of referral of patients to centers with facilities where lifesaving treatment like renal replacement therapy (haemodialysis, hemoperfusion, continuous Veno-venous hemofiltration) can be done on time to reduce the high mortality rate associated with it. Retrospective chart review of 10 patients admitted with paraquat poisoning at AIIMS Bhopal between March 2022 and March 2023. All patients presented 2-22 days post-ingestion, with amounts ranging from 10-100 ml. Common features included oral and gastrointestinal ulcers, hepatitis, acute kidney injury (AKI), and acute respiratory distress syndrome (ARDS). Hemodialysis was performed in two patients presenting within 3 days. Despite supportive therapy (steroids, N-acetylcysteine, renal replacement therapy), mortality was 100%, with ARDS being the universal cause of death. Paraquat poisoning carries a dismal prognosis with no survivors in our cohort. Early referral to tertiary care centers and timely initiation of renal replacement therapy may improve outcomes. Urgent public health measures and consideration of a ban are warranted.